Dietary carbohydrate intake, glycemic load, glycemic index and ovarian cancer risk in African-American women - Qin, Bo (Br J Nutr, 2015)
Epidemiologic evidence regarding the association between carbohydrate intake, glycemic load and glycemic index and risk of ovarian cancer has been mixed. Little is known about their impact on ovarian cancer risk in African-American women. Associations between carbohydrate quantity and quality and ovarian cancer risk were investigated among 406 cases and 609 controls using data from the African American Cancer Epidemiology Study (AACES). AACES is an ongoing population-based case-control study of ovarian cancer in African Americans in the US. Cases were identified through rapid case ascertainment and age- and site-matched controls were identified by random-digit-dialing. Dietary information over the year preceding diagnosis or the reference date was obtained using a food frequency questionnaire. Multivariable logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI) adjusted for covariates. The ORs comparing the highest quartile of total carbohydrate intake and total sugars intake versus the lowest quartile were 1.57 (95% CI 1.08, 2.28; p-trend=0.03) and 1.61 (95% CI 1.12, 2.30; p-trend<0.01) respectively. A suggestion of an inverse association was found for fiber intake. Higher glycemic load was positively associated with the risk of ovarian cancer (OR 1.18 for each 10 units/1,000 kcal; 95% CI 1.04, 1.33). No associations were observed for starch or glycemic index. Our findings suggest that high intake of total sugars and glycemic load are associated with greater risk of ovarian cancer in African-American women.